1998
DOI: 10.1515/zna-1998-1-208
|View full text |Cite
|
Sign up to set email alerts
|

Internal Cation Mobilities in Molten (K, Dy1/3)Cl

Abstract: Internal cation mobility ratios in the molten system KCl-DyCl 3 have been measured at 1093 K by Klemm's countercurrent electromigration method. From these, and data available on the conductivities and molar volumes of the mixtures, the internal mobilities b of both cations have been calculated. With increasing concentration of Dy, b K decreases. The decrease of b K is attributed to the tranquilization effect by Dy 3+ ions which strongly interact with Cl~ ions. With increasing concentration of K + , b Dy decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…1 with corresponding literature data for MCl-NdCl 3 systems (M: Li [7], Na [8] and K [5]). It is easy to notice, that ε increases with the increase of atomic number of alkali metal cation (its ionic radius) and y Nd , and reveals a maximum somewhere near equivalent fraction of NdCl 3 equal to 0.5 (it is equivalent to formula M 3 NdCl 6 or stoichiometry of NdCl 6 3− complex anion). It is reasonable to consider a very characteristic form of curve for the cesium system illustrates cumulated result of the diameter of cesium ion, its small polarization force and hence high stability of NdCl 6 3− complex anion (cesium ions are more mobile than other alkali metal ones in this relative scale in the NdCl 3 -deficient part of the system, and it quickly changes in the NdCl 3 -rich part; at the same time relative mobilities in other systems change moderately).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 with corresponding literature data for MCl-NdCl 3 systems (M: Li [7], Na [8] and K [5]). It is easy to notice, that ε increases with the increase of atomic number of alkali metal cation (its ionic radius) and y Nd , and reveals a maximum somewhere near equivalent fraction of NdCl 3 equal to 0.5 (it is equivalent to formula M 3 NdCl 6 or stoichiometry of NdCl 6 3− complex anion). It is reasonable to consider a very characteristic form of curve for the cesium system illustrates cumulated result of the diameter of cesium ion, its small polarization force and hence high stability of NdCl 6 3− complex anion (cesium ions are more mobile than other alkali metal ones in this relative scale in the NdCl 3 -deficient part of the system, and it quickly changes in the NdCl 3 -rich part; at the same time relative mobilities in other systems change moderately).…”
Section: Resultsmentioning
confidence: 99%
“…Arrangement of the migration quartz cell and details of experiments based on electrolysis of salt melts of required composition have been presented in papers reporting measurements of internal mobility of cations in MCl-LnCl 3 systems (M: Li, Na, K; Ln: La, Nd, Dy) [4][5][6][7][8]. The cell was modified by replacing reduction of gaseous chlorine to chloride ions on graphite electrode with electrodeposition of neodymium.…”
Section: Migration Cell and Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose we have developed py rochemical processes [1] such as countercurrent elec tromigration [2] and electrowinning [3-71, as was proposed by the Argonne National Laboratory [8], In addition, we have estimated the enrichment degree and investigated the electrochemical behavior of Cs in molten alkali ternary chloride [9 -11] and fluoride [11] systems by both experiment and Molecular Dy namics (MD) simulation. These results lead to the conclusion that it is rather difficult to enrich and re cover Cs in these systems, although we demonstrated that one can recover La3+ [12], Nd3+ [13], and Dy3+ [14,15]. There are other candidates for processes to function as inorganic ion exchangers [16][17][18].…”
Section: Introductionmentioning
confidence: 82%
“…La 3+ [5], Dy 3+ [6], and Nd 3+ [7] in a chloride bath. We have also estimated the limitation of the enrichment degree in alkali chloride and fluoride ternary [8,9] and quaternary [10] melts by molecular dynamics (MD) simulation.…”
Section: Introductionmentioning
confidence: 99%